2013
DOI: 10.1002/rcm.6721
|View full text |Cite
|
Sign up to set email alerts
|

Observation of CO2 and solvent adduct ions during negative mode electrospray ionization Fourier transform ion cyclotron resonance mass spectrometric analysis of monohydric alcohols

Abstract: The formation mechanisms of O3 and O4 adducts from monohydric alcohols in negative ion ESI FT-ICR MS were proposed. The solvent adduction effects can be eliminated or reduced by optimizing the collision energy of CID in FT-ICR MS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…[9] Inorganic anions solvated by methanol can be successfully detected by ESI-MS. [10] ESI-MS can be also used for detection of interaction between methanol and organic anions. [11][12][13] Interaction between methanol and anion may have an interesting practical implication. For example, solvation of inorganic anions may affect their separation selectivity upon capillary electrophoresis analysis.…”
Section: Dear Editormentioning
confidence: 99%
“…[9] Inorganic anions solvated by methanol can be successfully detected by ESI-MS. [10] ESI-MS can be also used for detection of interaction between methanol and organic anions. [11][12][13] Interaction between methanol and anion may have an interesting practical implication. For example, solvation of inorganic anions may affect their separation selectivity upon capillary electrophoresis analysis.…”
Section: Dear Editormentioning
confidence: 99%
“…Apart from monohydric alcohol (O 1 ) species, carboxylic acid (O 2 ) species, which represent the unseparated aromatic and olefinic components, unexpected O 3 , and even O 4 ionic species are also present. Previous research has discussed the formation of O 3 ionic species from monohydric alcohols through addition reactions with other species and the formation of O 4 ionic species from O 3 species with the addition of a solvent alcohol molecule 62 (the distribution of O 2 , O 3 , and O 4 compounds are shown in the Supporting Information). Figure 8b shows isoabundance plots of double bond equivalence (DBE) as a function of the carbon number for the O 1 compounds obtained from negative ESI Orbitrap MS in SD feed and its SFE fractions.…”
Section: Variation Of Normal Paraffin Composition In Sfe By Gc−msmentioning
confidence: 99%
“…Atmospheric pressure chemical ionization (APCI) is an effective ionization source for the characterization of saturated hydrocarbons. However, as a result of its ionization mechanism, it leads to the generation of fragment ions that affect the overall judgment. , Electrospray ionization (ESI) is a soft ionization technique for detailed characterization of polar compounds in petroleum without fragment ions. However, hydrocarbons are nonpolar compounds that cannot be directly ionized by ESI. Ruthenium-ion-catalyzed oxidation (RICO) has been used to transform saturated hydrocarbons into alcohols and ketones, and it can also convert aromatic-attached aliphatic appendages and alkenes to their carboxylic acid derivatives, which can be analyzed by negative ESI HRMS. Zhou et al , characterized the monohydric alcohols (O 1 ) in the products obtained from the RICO oxidation reactions and RICO–LiAlH 4 reduction reactions by negative ESI FT-ICR MS. The results were in agreement with those analyzed by field ionization gas chromatography time-of-flight mass spectrometry (FI GC–TOF MS), which meant that it could be used as a potential semi-quantitative analysis for saturates.…”
Section: Introductionmentioning
confidence: 99%
“…Phenolic compounds are also important acidic species in petroleum that can be characterized along with naphthenic acids through (−)­ESI . The O1 class species (having only one oxygen heteroatom in the molecules) in (−)­ESI mass spectra could be phenols and alcohols; however,alcohols are not easily ionized by (−)­ESI and could be suppressed by acids . In addition, the O1 class species assigned from (−)­ESI mass spectra usually have the most abundant series with a minimum DBE value of 4, which implies that they are alkyl phenols.…”
Section: Applications For Polar Compoundsmentioning
confidence: 99%
“…109 It was found that monohydric alcohols in the RICO product can form O3 and O4 adduct ions in (−)ESI, which could mislead the interpretation of the composition analysis of the alcohols, especially when they are in a complex mixture. 106 The O3 adducts are formed by the coupling of a monohydric alcohol ion with CO 2 . The O4 species are formed by the adducting of O3 ionic species with an alcohol molecule of the solvent, such as methanol or ethanol.…”
Section: Approaches and Applications Formentioning
confidence: 99%